Chemo-Enzymatic Synthesis of Antagonists of the Myelin-associated Glycoprotein (MAG) - Gan-Pan Gao; Oliver Schwardt; Tamara Visekruna; Said Rabbani; Beat Ernst (CHIMIA, 2004)
Ganglioside GQ1b ? is the most potent antagonist of the Myelin-associated glycoprotein (MAG) identified so far. For the efficient synthesis of the partial structure of GQ1b ? and derivatives thereof, a chemo-enzymatic strategy using the ?(2?3)-sialyltransferase ratST3Gal III (EC 2.4.99.6) was applied. Besides the natural substrates Gal? (1?3)GlcNAc (19) and Gal? (1?4)GlcNAc (20), the disaccharides Gal? (1?3)GalNTCA?-OSE (9), Gal? (1?3)GalNAc?-OSE (11), and Gal? (1?3)Gal?-OSE (14) were also tolerated by the enzyme and were transformed to the target structures in preparative scale.